Risk prediction for <1 cm lateral lymph node metastasis in papillary thyroid microcarcinoma - Zhang, Chengxin; Fu, Siqi; Liu, He; Xue, Shuai (Frontiers in Endocrinology, 2023)
Background: Because the diameter of the suspicious lymph nodes is less than 1 cm and adjacent to important structures in the neck, the diagnosis of small LLNM is important but difficult without the help of fine needle aspiration (FNA). There are no relevant reports of risk factors that predict the risk of suspicious <1 cm LLNM.Methods: A total of 159 PTMC patients with suspicious <1 cm LLNM were included in the study. Multivariate logistic regression analysis was used to identify ultrasound independent predictors of LLNM. A predictive model was developed according to multivariate logistic regression and evaluated by Hosmer-Lemeshow fit test.